(untitled) (Scientia Agropecuaria, 2023)
Coffee leaf rust (Hemileia vastatrix) is the most important disease in coffee crops around the world. Currently, there is limited knowledge about mass production methodologies and ex-situ infection of H. vastatrix that lead to the development of different health characterization studies of Coffea or disease phenotyping. In this context, the aim of this research was to develop a simple protocol for the mass production of coffee rust uredospores under controlled conditions and to determine their infection in coffee seedlings. Uredospores of H. vastatrix were collected from infected plants in the “Chontal” coffee-growing area in San Martín, Peru. The viability of uredospore germination was evaluated, and a uredospores suspension (2 x 105 uredospores/mL) was prepared to inoculate coffee seedlings. Incidence and sporulation rates were evaluated after 43 days of inoculation. During the multiplication process of H. vastatrix uredospores, using controlled conditions (23±1 °C, ≈ 80% relative humidity and photoperiod of 16 hours of light) under an innovative system, the first symptoms of chlorosis were observed on coffee leaves 20 days after inoculation. Our findings show a 100% incidence of inoculated coffee plants with an average of 54 mg of H. vastatrix uredospores per plant and a 1.38 x 10-1 mg/cm2 sporulation rate. Finally, here we report a protocol that allows mass multiplication of H. vastatrix uredospores under controlled conditions, that would be useful in any time for coffee leaf rust bioassays.